Predictors of Asylum Seekers’ Health Care Utilization in the Early Phase of Resettlement - Kindermann, David; Zeyher, Valentina; Nagy, Ede; Friederich, Hans-Christoph; Bozorgmehr, Kayvan; Nikendei, Christoph (Frontiers in Psychiatry, 2020)
Background: Asylum seekers display high prevalence rates of posttraumatic stress disorder, depression, anxiety, and panic disorder due to pre- and peri-migration stressors. In contrast, health care utilization among asylum seekers in the early phase of resettlement is low. However, the early stages after migration are a particularly vulnerable phase in which psychosocial support measures are needed to prevent mental disorders from becoming chronic. Objective: To identify predictors of asylum seekers’ health care utilization in the early stages of resettlement. Methods: Using stepwise regression analysis, the variance explanation of the (1) total utilization of health care services as well as the individual utilization of (2) outpatient psychiatrists, (3) counselling centers for mental health, and (4) general practitioners was analyzed in n= 65 asylum seekers in a longitudinal study. Follow-up assessment took place between three to five months after baseline assessment. We defined a) the sociodemographic variables gender, age, origin, parenthood, religion, language proficiency and b) the psychological variables sense of coherence and emotion regulation as well as c) the asylum seekers’ psychiatric diagnoses at baseline as possible predictors. Results: Individual sociodemographic factors, such as age, number of children, origin, language proficiency in English or German as well as the emotion regulation strategies of expressive suppression and cognitive reappraisal, sense of coherence, and a diagnosis of PTSD were shown to be predictive for the utilization of health care services among asylum seekers. Conclusions: Low-threshold, culture-sensitive treatment offers and language courses for asylum seekers should be established in the early phase after migration. General practitioners should be a central hub for further referrals to disorder-specific treatments.